N6-methyladenosine with immune infiltration and PD-L1 in hepatocellular carcinoma: novel perspective to personalized diagnosis and treatment - Shi, Yanlong; Wang, Yizhu; Zhang, Wenning; Niu, Kaiyi; Mao, Xinyu; Feng, Kun; Zhang, Yewei (Frontiers in Endocrinology, 2023)
Background Increasing evidence elucidated N6-methyladenosine (m6A) dysregulation participated in regulating RNA maturation, stability, and translation. This study aimed to demystify the crosstalk between m6A regulators and the immune microenvironment, providing a potential therapeutic target for patients with hepatocellular carcinoma (HCC). Methods Totals of 371 HCC and 50 normal patients were included in this study. GSE121248 and GSE40367 datasets were used to validate the expression of HNRNPC. The R package “ConsensusClusterPlus” was performed to screen consensus clustering types based on the expression of m6A regulators in HCC. The R package “pheatmap”, “immunedeconv”, “survival”, “survminer” and “RMS” were applied to investigate the expression, immunity, overall survival, and clinical application in different clusters and expression groups. Comprehensive analysis of HNRNPC in pan-cancer was conducted by TIMER2 database. Besides, HNRNPC mRNA and protein expression were verified by qRT-PCR and immunohistochemistry analysis. Results Most of m6A regulators were over-expressed excerpt for ZC3H13 in HCC. Three independent clusters were screened based on m6A regulators expression, and the cluster 2 had a favorable prognosis in HCC. Then, the cluster 2 was positively expression in macrophage, hematopoietic stem cell, endothelial cell, and stroma score, while negatively in T cell CD4+ memory and mast cell. We identified HNRNPC was an independent prognostic factor in HCC, and nomogram performed superior application value for clinical decision making. Moreover, PD-L1 was significantly up-regulated in HCC tissues, cluster 1, and cluster 3, and we found PD-L1 expression was positively correlated with HNRNPC. Patients with HCC in high-expression groups was associated with tumor-promoting cells. Besides, HNRNPC was correlated with prognosis, TMB, and immune checkpoints in cancers. Particularly, the experiments confirmed that HNRNPC was positively expression in HCC cells and tissues. Conclusion The m6A regulators play irreplaceable roles in prognosis and immune infiltration in HCC, and the relationship of HNRNPC and PD-L1 possesses a promising direction for therapeutic targets of immunotherapy response. Exploration of m6A regulators pattern could be build the prognostic stratification of individual patients and move toward to personalized treatment.